The efficacy and safety of fractional radiofrequency nanoneedle system in the treatment of atrophic acne scars in Asians - Sunatra Nitayavardhana (2020)
© 2020 Wiley Periodicals LLC Background: Multiple treatment modalities have been developed to treat atrophic acne scars with varying degrees of success. Post-inflammatory hyperpigmentation (PIH) after acne scar treatments remain a major concern in Asian patients. Fractional radiofrequency (FRF) has been used in many dermatological skin conditions including acne scars. Aims: To determine the efficacy and safety of FRF nanoneedle system in the treatment of acne scars in Asians. Methods: This is a prospective, evaluator-blinded study with 25 subjects diagnosed with moderate to severe acne scarring. All subjects received 3 monthly treatments of the FRF nanoneedle system on both cheeks. Primary outcome was the clinical improvement of acne scars graded by 2 blinded dermatologists at baseline, 1-, 3-, and 6-month follow-ups. Objective scar volume analysis was done using ultraviolet A (UVA) light video camera. Subjects’ self-assessment, pain score, and adverse events were also recorded. Results: Twenty-three out of 25 subjects completed the study and attended all follow-up. Clinical improvement of acne scars was observed as early as 1-month follow-up. Objective evaluation of acne scar volume decreased significantly on all follow-up compared to baseline (P <.005). Majority of the subjects (48%) reported marked improvement in their acne scars. Adverse events such as pain, erythema, burning sensation, edema, scab formation, and PIH were mild and temporary. Conclusions: FRF nanoneedle system is a safe and effective treatment for acne scars in Asians. However, despite the significant changes in the scar volume, caution should be used to avoid excessive coagulation resulting in PIH.